prime minister decree 1267/2016 amending prime minister decree 1272/2015.on setting up the ministerial committee for investment dispute settlement - Egypt (2025)
Prime Minister Decree No. 1267 of the year 2016 – قرار رئيس مجلس الوزراء رقم 1267 لسنة 2016